Działania wspierające innowacyjność jako czynnik rozwoju województwa wielkopolskiego - Gałganek-Napierała, Monika (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
At present, innovation has become mainstream in creating competitiveness, whether at the level of local governments and enterprises or at the national and European Union levels. Moreover, innovation is believed to be much more than a one-off transfer of research results into the small and medium enterprises sector. Nowadays, innovation is perceived as a peculiar philosophy which concerns everybody, where local government has a particular role to play as an institution to grant financial support in the new financial perspective of 2007–2013. Today, in the process of globalization, margins for products and services, lower gross profit, and the need for revenue growth and cost reduction – innovation is essential to ensure the competitiveness of the region. Innovation is the catalyst for the region’s growth, and supporting it must become a significant task for all levels of regional management, including the scientific world, business support institutions and the whole community. “Europe has a proud tradition of inventing solutions that have improved people’s lives all over the world… innovation is the key to tackling the main challenges we face now”.